Pengaruh Experiental Marketing terhadap Repurchase Intention melalui Experiental Value pada Maskapai Penerbangan Garuda di Indonesia - Kusuma, Andrey Adhy (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Experiential marketing is the core element for delivering and creating value for customers through marketing approach. It could help to create sustainable growth and excellence to promote business. The research aims to know the influence of experiential marketing, experiential value and purchase intention on Garuda Indonesia flight service in Surabaya. In this study used is the conclusive research on the study of experimental or causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 people consumers of Garuda Indonesia in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that the experiential marketing effect directly against the experiential value and purchase intention. In addition, the study found that the relationship between experiential marketing and purchase intention, can be strengthened by mediator experiential value. Ultimately experiential value found also have influence on the purchase intention